2000
DOI: 10.2460/javma.2000.217.681
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of stanozolol in cats

Abstract: Results suggest that stanozolol is hepatotoxic in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
0
9
0
4
Order By: Relevance
“…Perioperative bleeding tendencies, however, were not commonly reported in dogs undergoing biliary surgery in these studies . The finding that prolongations in PT or aPTT carry prognostic significance suggests the coagulation changes may represent hepatic synthetic failure or the presence of DIC rather than vitamin K deficiency …”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 72%
See 1 more Smart Citation
“…Perioperative bleeding tendencies, however, were not commonly reported in dogs undergoing biliary surgery in these studies . The finding that prolongations in PT or aPTT carry prognostic significance suggests the coagulation changes may represent hepatic synthetic failure or the presence of DIC rather than vitamin K deficiency …”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 72%
“…Studies evaluating coagulation testing and bleeding tendencies in cats with hepatobiliary disease, the majority of which have cholestatic disorders (eg, cholangitis, hepatic lipidosis), have shown that alterations in coagulation profile are common (45–73% of cases) . Most of these studies have concluded on the basis of the presence of PIVKA (protein invoked by vitamin K absence), FVII analysis, or by response to therapy that the majority of these cats had a vitamin K dependent coagulopathy rather than hepatic synthetic failure . It is important to note that 22% of the cats in one of these studies with abnormal coagulation tests did have increased bleeding tendencies, all of which were associated with provocative procedures, such as venipuncture or intravenous catheter placement .…”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 99%
“…Stanozolol is an anabolic steroid that has been associated with both an acute ALI as well as delayed fatal ALF during a 4 week clinical trial of 21 cats. Cats with gingivitis and stomatitis were more likely to develop delayed ALF …”
Section: Etiologymentioning
confidence: 99%
“…Acute hepatic injury may be caused by a direct toxic effect of the drug or its metabolites on the hepatocyte, producing a predictable dose-dependent effect, or by idiosyncratic drug reactions, which occur unpredictably in a small number of cats exposed to a particular drug such as diazepam (Lappin, 2001). Harkin et al (2000) suggested that stanozolol was hepatotoxic in cats.…”
Section: Introductionmentioning
confidence: 99%